Techno-Prosthetic Romantic Futurism - Youngquist, Paul (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractCyberspace creates new ecologies for scholarship: information displaces interpretation, argument cedes to association, and possibility disturbs certainty. What happens, then, when Romanticism goes digital? Rather than answer that question the piece that follows performs it. A hundred little paragraphs, interlinked and unfettered, open a field of digital inquiry where one possibility gives rise to another, and another, and another, and . . . . Skimming/scanning replaces reading as a means of communication. Hacking becomes another word for criticism, and you become a player in the game of digital scholarship. As you confront the possibilities Romanticism raises, your responses conjure various futures. In this particular version of the game such possibilities include virtual subjects, digital territories, raced relations, hacked classics, and mixed messages. The futures they provoke are yours to imagine. Point, click, and perform “Techno-Prosthetic Romantic Futurism.”